Utilization of ChatGPT in Dental Healthcare (Academia Journal of Medicine, 2024)
The integration of artificial intelligence (AI) in the field of  dentistry has been gaining prominence, with Chatbot  Generative Pretrained Transformer (ChatGPT), emerging as  a pivotal tool. ChatGPT's applications span a myriad of  functionalities including diagnostic aid, educational  support, and patient interaction.
Keywords: ChatGPT; Dentistry; Application